2017
DOI: 10.1016/j.immuni.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Dicer Deficiency Differentially Impacts Microglia of the Developing and Adult Brain

Abstract: Microglia seed the embryonic neuro-epithelium, expand and actively sculpt neuronal circuits in the developing central nervous system, but eventually adopt relative quiescence and ramified morphology in the adult. Here, we probed the impact of post-transcriptional control by microRNAs (miRNAs) on microglial performance during development and adulthood by generating mice lacking microglial Dicer expression at these distinct stages. Conditional Dicer ablation in adult microglia revealed that miRNAs were required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 79 publications
2
71
0
Order By: Relevance
“…Another possible explanation for the neuroimmune modulatory function of CCL17 is that systemic production of CCL17 by immune cells outside the CNS influences the recruitment of myeloid cells into the brain and indirectly also alters microglia morphology. When examining hematopoietic cells in the CNS, we detected CCL17/EGFP-producing cells only within the DC/Mφ population but not in microglia ( Figure 5 and Supporting Information Figure S6), whereas CCL17 mRNA was previously described to be also expressed in microglia, particularly under certain conditions of activation (Schwarz et al, 2013;Varol et al, 2017). In this context, it is of interest that CCL17 deficiency led to a notable decrease in the total number of brain resident CD45 int microglia, which was already visible in steady state but more pronounced after systemic LPS stimulation ( Figure 5).…”
Section: Ccl17 Affects Synaptic Transmission In the Ca1 Regionmentioning
confidence: 78%
See 1 more Smart Citation
“…Another possible explanation for the neuroimmune modulatory function of CCL17 is that systemic production of CCL17 by immune cells outside the CNS influences the recruitment of myeloid cells into the brain and indirectly also alters microglia morphology. When examining hematopoietic cells in the CNS, we detected CCL17/EGFP-producing cells only within the DC/Mφ population but not in microglia ( Figure 5 and Supporting Information Figure S6), whereas CCL17 mRNA was previously described to be also expressed in microglia, particularly under certain conditions of activation (Schwarz et al, 2013;Varol et al, 2017). In this context, it is of interest that CCL17 deficiency led to a notable decrease in the total number of brain resident CD45 int microglia, which was already visible in steady state but more pronounced after systemic LPS stimulation ( Figure 5).…”
Section: Ccl17 Affects Synaptic Transmission In the Ca1 Regionmentioning
confidence: 78%
“…Thus, Ccl17 expression in neurons and hematopoietic cells is differentially regulated, possibly depending on the different cytokine receptor expression. When examining hematopoietic cells in the CNS, we detected CCL17/EGFP-producing cells only within the DC/Mφ population but not in microglia ( Figure 5 and Supporting Information Figure S6), whereas CCL17 mRNA was previously described to be also expressed in microglia, particularly under certain conditions of activation (Schwarz et al, 2013;Varol et al, 2017). In our LPS-induced model of systemic inflammation and in the EAE model (Ruland et al, 2017), we observed a reduction in the total number of brain infiltrating CD45 hi DC/Mφ, which may result from an impaired ability of Ccl17-deficient DC to immigrate into the CNS (Ruland et al, 2017;Stutte et al, 2010).…”
Section: Ccl17 Affects Synaptic Transmission In the Ca1 Regionmentioning
confidence: 78%
“…ADP is the endogenous ligand of P2Y12, and homeostatic microglia have increased ligand-mediated calcium responses, which are blocked by selective P2Y12 antagonism (87). that distinguish resident microglia from peripheral mononuclear cells/macrophages (50-52) include FSRSL, P2Y12, TMEM119, CX3CR1, Siglec-H, and the microRNAs miR-99a, miR-125-5p, and miR-342-3p, which are highly expressed in both mouse and human microglia (50,53). Homeostatic microglia are dependent on TGF-β, and CNS-specific TGF-β-KO mice develop late-onset motor dysfunction (50), which may be due to impairment of microglia-associated glutamate recycling and synaptic plasticity (54).…”
Section: Immune Cells Involved In Neurodegenerationmentioning
confidence: 99%
“…The impact of miRNAs on microglial phenotype has been recently revealed by generating mice lacking microglial Dicer, an enzyme necessary for miRNA maturation. Dicer ablation resulted in hyperresponsiveness of adult microglia to stimuli (peripheral endotoxin), indicating that miRNAs overall limit microglia responses to challenge (Varol et al, 2017). A number of studies dissected the role of specific miRNAs in microglia (Guedes, Cardoso, & Pedroso de Lima, 2013;Karthikeyan, Patnala, Jadhav, Eng-Ang, & Dheen, 2016;Ponomarev, Veremeyko, & Weiner, 2013).…”
Section: Molecular Mechanisms Linking Receptor/channel Activation Tmentioning
confidence: 99%